Palladium-catalyzed methylene C(sp3)–H arylation of the adamantyl scaffold1. Issue 10 (14th October 2015) - Lao, Ye-Xing; Wu, Jia-Qiang; Chen, Yunyun; Zhang, Shang-Shi; Li, Qingjiang; Wang, Honggen
<x xml:space="preserve">Abstract</x> A palladium-catalyzed C(sp3)–H arylation of adamantane at the methylene position with the assistance of an amide group was developed.